2019
DOI: 10.1136/bjophthalmol-2019-314572
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of blindness and visual impairment; and cataract surgical services in Katsina state of Nigeria

Abstract: AimTo generate data on blindness and visual impairment for planning and monitoring a comprehensive eye care programme in Katsina state of Nigeria.MethodA rapid assessment of avoidable blindness (RAAB) survey methodology was used to select 3120 persons aged 50 years and over. The sample was selected using a multistage cluster randomised sampling. Each participant had visual acuity and lens assessment. Persons with vision less than 6/12 in any eye were assessed for the cause of visual impairment. Persons with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 7 publications
0
19
4
3
Order By: Relevance
“…The prevalence of blindness and VI in Nigeria were reported to be 6.1% and 4.2%, respectively [ 12 ], which was significantly higher than reported globally [ 5 ]. Studies [ 10 , 12 , 14 , 15 ] conducted in different parts of Nigeria indicated that the prevalence of blindness and VI is highest in the north–east (8.2% and 6.9%) and lowest in the south–west (2.8% and 3.3%) part of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of blindness and VI in Nigeria were reported to be 6.1% and 4.2%, respectively [ 12 ], which was significantly higher than reported globally [ 5 ]. Studies [ 10 , 12 , 14 , 15 ] conducted in different parts of Nigeria indicated that the prevalence of blindness and VI is highest in the north–east (8.2% and 6.9%) and lowest in the south–west (2.8% and 3.3%) part of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In similar surveys done elsewhere in Nigeria, a higher overall blindness prevalence of 4.5%, 4.2%, and 5.4% was reported in Birnin-Kebbi,[ 12 ] Plateau,[ 13 ] and Katsina,[ 14 ] respectively. In other regions of Sub-Saharan Africa, blindness prevalence from similar population-based surveys varied from 3.3% in Southern Malawi[ 15 ] to 1.8% in Western Rwanda.…”
Section: Discussionmentioning
confidence: 80%
“…In Katsina state, northern Nigeria, 1999, glaucoma was the fourth cause of blindness representing 5.8% of all causes 49 . In the same state, almost two decades after the first study, glaucoma was the third cause of blindness and represented 7.0% of all cases 50 . In Kuolikoro, Mali, glaucoma was the third cause of blindness (7.8%) in 2008.…”
Section: Rapid Studiesmentioning
confidence: 99%
“…49 In the same state, almost two decades after the first study, glaucoma was the third cause of blindness and represented 7.0% of all cases. 50 In Kuolikoro, Mali, glaucoma was the third cause of blindness (7.8%) in 2008.…”
Section: Rapid Studiesmentioning
confidence: 99%